PENGGUNAAN METODE KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SDN 021 TANJUNG PALAS KECAMATAN DUMAI TIMUR - Sejati ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This research was motivated by the low result of fifth grade students learn math SDN 021 Tanjung Palas. The low learning outcomes due to: (a) students find it difficult to understand the elements and properties of geometrical abstract; (B) how to deliver materials that are lacking attract students to understand the material I teach, always using methods lectures, discussion, assignments. This study aims to improve the learning outcomes of mathematics through STAD cooperative method. This research is a class act, carried out by two cycles. The study states that hasila learning has increased, this is evidenced by the base score is the number of students who completed 16 students (44.4%), in the first cycle is the number of students who pass the 25 students (69.4%). And the second cycle is the number of students who pass the 32 students (88.9%).